1968
DOI: 10.1037/h0025721
|View full text |Cite
|
Sign up to set email alerts
|

A review of research on imitative behavior.

Abstract: Focusing on imitation in the dyad, where 1 observer (0) imitates 1 model (M), this review concerns causal relations between M's behavior and O's imitation of M's behavior. First, findings are reviewed in a manner relatively independent of processes hypothesized to mediate imitation; then theoretical viewpoints about imitation are evaluated. An extension of the best available viewpoint, that of Bandura, is presented. Finally, gaps in the literature are enumerated along with suggestions for subsequent research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
1
1

Year Published

1973
1973
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(108 citation statements)
references
References 153 publications
3
103
1
1
Order By: Relevance
“…These results suggest that the effects of teacher role modelling may be attenuated in intervention programmes where peers model incompatible behaviours (eg by eating other snacks rather than fruit and vegetables). Research has also shown, in contexts other than that of food consumption, that children are more likely to imitate a model whose behaviour they see being rewarded (Flanders, 1968), or who is of the same age or slightly older than themselves (Brody & Stoneman, 1981), or who they like or admire (Bandura, 1977). They are also more likely to imitate the behaviour of multiple rather than single models (Fehrenbach et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the effects of teacher role modelling may be attenuated in intervention programmes where peers model incompatible behaviours (eg by eating other snacks rather than fruit and vegetables). Research has also shown, in contexts other than that of food consumption, that children are more likely to imitate a model whose behaviour they see being rewarded (Flanders, 1968), or who is of the same age or slightly older than themselves (Brody & Stoneman, 1981), or who they like or admire (Bandura, 1977). They are also more likely to imitate the behaviour of multiple rather than single models (Fehrenbach et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown to be particularly effective when the model has his or her behaviour rewarded (Flanders, 1968), is the same age or slightly older than the child (Brody and Stoneman, 1981), and is liked or admired by the child (Bandura, 1977). The likelihood of imitation is also increased with the use of multiple as opposed to single models (Fehrenbach et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Most social influence research, whether involving conformity (e.g., Cooper, 1979;Thelen, Frautschi, Roberts, Kirkland, & Dollinger, 1981), compliance techniques (e.g., Cialdini, 2001), or modeling (e.g., Bandura, 1986;Flanders, 1968), has been concerned with influence in the positive direction, that is, with factors that make it more likely a person will adopt an attitude or perform a behavior similar to that of others (hereafter referred to as positive modeling). Although the reasons model-observer similarity augments positive modeling are not fully understood, informational and normative influences are likely involved.…”
mentioning
confidence: 99%